Nice couple, funny couple, happy couple: emotional intelligence, humor style, and relationship satisfaction - Sunil, Niya Treza; Jegathesan, Anasuya Jegathevi; Prihadi, Kususanto Ditto (International Journal of Public Health Science (IJPHS), 2024)
This study explores the interplay of emotional intelligence (EI), beneficial humor styles (BHS), and relationship satisfaction (RS) within romantic relationships. Drawing on the social exchange theory, it examines whether BHS mediate the relationship between EI and RS. Data was collected from individuals aged 18 to 65 in romantic relationships, and analyses were conducted using bootstrapping methods. Results reveal a significant positive direct effect of EI on RS. However, the mediation analysis suggests that BHS do not mediate the relationship between EI and RS, indicating that EI's impact on RS remains independent of humor styles. These findings underscore the distinct and substantial roles of EI and BHS in predicting RS. While both factors contribute to RS, they do so independently. This study enhances our understanding of the multifaceted factors influencing romantic relationship dynamics and highlights the importance of emotional intelligence and humor styles in fostering relationship satisfaction. Limitations include self-report measures and a limited age range, suggesting the need for further research to explore these dynamics across diverse populations.